SEMANTIC TYPES OF DERIVATIVE BASES OF DERIVATIVE NOUNS WITH LATIN SUFFIXES FOR THE DESIGNATION OF PERSONS IN THE GERMAN AND UZBEK LANGUAGES - Babaev Mahmud Tashpulatovich (Galaxy International Interdisciplinary Research Journal, 2022)
The relevance of the article is determined by its focus on the study of word formation processes based on the functional load of word stems. Insufficient study of the word-formation ability of educational foundations stimulates the need to study their semantic properties, which allows the formation of new units. The aim of the study is to determine the semantic types of the basis of the studied derivative nouns in the German and Uzbek languages, to establish their common and distinctive features. The material of the article is derived nouns with Latin suffixes in German and Uzbek, containing in their semantic structure the lexical-categorical meaning of a person.